Funcionamiento familiar y maltrato infantil en escolares, 2019 - Avila Reyes, Katerini Paola (2019)
The present investigation of descriptive-correlational design of quantitative approach, had like objective to study the relation that exists between the familiar operation and the infantile abuse: physical, psychological, sexual and by negligence in scholastic. The sample consisted of 105 schoolchildren from the fourth, fifth and sixth grade of primary education. Two questionnaires were used in the data collection: Olson's family functioning level assessment scale modified by Martínez and the scale of child mistreatment in schoolchildren elaborated by Trigoso modified by the study authors. The results are presented in simple and double entry statistical tables. The following findings were found: 79.0 percent of schoolchildren presented psychological abuse, 77.0 percent presented physical abuse, 56.0 percent presented abuse through negligence, and 3.8 percent presented sexual abuse. Regarding the level of family functioning, it was found that 63.8 percent of school children have a high functional family, while 34.3 percent had an intermediate family functioning, and 1.9 percent had a family functioning low. There is a significant relationship between family functioning and child abuse: physical, psychological and negligence, not being so with sexual abuse.